Fine’s McTaggart: Reloaded - Roberto Loss (Manuscrito)
ABSTRACT In this paper I will present three arguments (based on the notions of constitution, metaphysical reality, and truth, respectively) with the aim of shedding some new light on the structure of Fine’s (2005, 2006) ‘McTaggartian’ arguments against the reality of tense. Along the way, I will also (i) draw a novel map of the main realist positions about tense, (ii) unearth a previously unnoticed but potentially interesting form of external relativism (which I will label ‘hyper-presentism’) and (iii) sketch a novel interpretation of Fine’s fragmentalism (which I contrast with Lipman’s 2015, 2016b, forthcoming).